OBSERVATION OF CHANGES IN PHYSICAL PROPERTIES IN THE LONGISSIMUS DORSI MUSCLE IN POST-SLAUGHTER CATTLE DURING COLD STORAGE (DISPLAY) (Jurnal Peternakan Lingkungan Tropis, 2021)
Changes in physical properties that are usually found in beef are changes in the pH value of post- slaughter cattle, where the pH of beef is 5.4-5.7. Value of water holding capacity (DIA) / water holding capacity, namely water that is bound by the ability of meat. Cooking loss is an indicator that determines the nutritional value of meat where the weight of the meat is calculated based on the weight of the meat lost during cooking/heating. Color, where meat that has good quality and is most preferred by consumers is meat that has a bright red color. The meat or muscle of Longissimus Dorsi before being processed further, the first thing to do is the meat is taken from the Slaughterhouse (RPH). The meat is put in a box, then put in a refrigerator at 40C. This study was conducted to determine changes in physical properties that occur in meat. This research was conducted at the Faculty of Agriculture, Mulawarman University on 12-18 April 2021. The research experiment used a Completely Randomized Design (CRD) with 4 treatments and four replications. The data were analyzed using variance (ANOVA) and further tested using Duncan's Multiple Range Test (UJBD). This study showed that beef that the pH value was significantly different in each treatment (p0.05).
Keywords: Array; Array